Management culture as part of the organizational culture in the formation and implementation of the organization's strategy - G. Zi (Вестник университета)
The article theoretically substantiates the importance of the category “management culture” as part of the organizational culture in the formation and implementation of the organizations strategy and separately considers some of its elements. The paper presents the categories and subcategories of management culture: strategy, organizational structure, regulation, technology, information systems, control, incentives. The study analyses the importance of the strategy as one of the elements of the management culture and the ratio of goals. The paper evaluates the factors that determine the success of planning and implementing the strategy. The article pays special attention to the discussion of information technologies as one of the elements of management culture, intensity and options for the development and implementation of modern technologies in business process management. When discussing processes as one of the elements of the management culture, the author emphasizes the complexity of managing processes and the importance of their consistency for achieving the goals of the organization. The study concludes, that the main role of management is to achieve the goals of the company using a certain number of employees, management methods and controls, which are regulated by the management culture, which is an integral part of the organizational culture of the company.